Circadian clock, cell division, and cancer: from molecules to organism - Shostak, Anton (International journal of molecular sciences, 2017)
As a response to environmental changes driven by the Earth’s axial rotation, most organisms evolved an internal biological timer—the so called circadian clock—which regulates physiology and behavior in a rhythmic fashion. Emerging evidence suggests an intimate interplay between the circadian clock and another fundamental rhythmic process, the cell cycle. However, the precise mechanisms of this connection are not fully understood. Disruption of circadian rhythms has a profound impact on cell division and cancer development and, vice versa, malignant transformation causes disturbances of the circadian clock. Conventional knowledge attributes tumor suppressor properties to the circadian clock. However, this implication might be context-dependent, since, under certain conditions, the clock can also promote tumorigenesis. Therefore, a better understanding of the molecular links regulating the physiological balance between the two cycles will have potential significance for the treatment of cancer and associated disorders.